Pendidikan Inklusif bagi Anak Berkebutuhan Khusus (ABK) di MI Almaarif 02 Singosari Malang - Abidah, Faizah Nurul (Maliki Interdisciplinary Journal, 2025)
Children with Special Needs (ABK) are children who have unique characteristics and are different from children in general. In other words, they may experience challenges in mental, emotional, or physical aspects. The ABK category includes the blind, hearing impaired, mentally retarded, physically disabled, hearing impaired, learning difficulties, autism, and behavioral difficulties. Because of the obstacles in education faced by these children, they need educational services that are tailored to their individual abilities and potential. Therefore, this research took place when I was still a teaching assistant in class 5A at MI Almaarif 02 Singosari. This child has autism and his classmates say he often causes trouble. The results of this research at his school received special marks from teachers at MI Almaarif 02 Singosari Malang.